2013
DOI: 10.1002/jor.22419
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and early diagnosis of orthopedic device‐related infection by microbial heat production and sonication

Abstract: Proper and rapid diagnosis of orthopedic device-related infection is important for successful treatment. Sonication has been shown to improve the diagnostic performance. We hypothesized that the combination of sonication with a novel method called microcalorimetry will further improve and accelerate the diagnosis of implant infection. We prospectively included 39 consecutive patients (mean age 59 years, 62% males) at our institution from whom 29 orthopedic prostheses and 10 osteosynthesis material were explant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 15 publications
3
42
0
Order By: Relevance
“…The identification of the causative microorganisms solely by tissue cultures has been unhelpful in a large proportion of cases, particularly in those with previous use of antibiotics (10). For this reason, several researchers have applied a sonication (low-intensity ultrasound) technique to displace microorganisms from the surface of removed prosthetic devices, and they eventually were able to demonstrate an increase in the rate of etiological diagnosis compared to that with periprosthetic tissue cultures (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Since skincontaminating bacteria produce many osteosynthesis infections, comparing the sonication results of prosthetic joint infection to those of fracture fixation infections is not an easy task.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of the causative microorganisms solely by tissue cultures has been unhelpful in a large proportion of cases, particularly in those with previous use of antibiotics (10). For this reason, several researchers have applied a sonication (low-intensity ultrasound) technique to displace microorganisms from the surface of removed prosthetic devices, and they eventually were able to demonstrate an increase in the rate of etiological diagnosis compared to that with periprosthetic tissue cultures (11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Since skincontaminating bacteria produce many osteosynthesis infections, comparing the sonication results of prosthetic joint infection to those of fracture fixation infections is not an easy task.…”
Section: Discussionmentioning
confidence: 99%
“…Since skincontaminating bacteria produce many osteosynthesis infections, comparing the sonication results of prosthetic joint infection to those of fracture fixation infections is not an easy task. Few of these previous studies evaluated the role of sonication in the microbiological diagnosis of osteosynthesis infections (17,20,22,26,27). Holinka et al (20) sonicated only six osteosynthesis devices and therefore could not draw any conclusions regarding the advantage of sonication compared to conventional techniques (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meticulous treatment plan is warranted to provide the patient the best possibilities for a successful outcome. PCR-based methods as well as sonication may be valuable tools in the proper diagnostics of an implant-related infection (Borens et al 2013). Fracture union should be the most important aspect when deciding the proper treatment path.…”
Section: Future Aspectsmentioning
confidence: 99%
“…Previous studies have shown that liquid cultures seem to provide better conditions to sessile bacterial growth than solid media (9,10). As already shown in previous studies addressing OIAI and prosthetic joint infection, Gram-positive bacteria were the most common sessile pathogens isolated in SC (60.6%) and SMF (72.7%), followed by Gram-negative bacilli, which have been increasingly identified among subjects presenting OIAIs (3,11). Our study had limitations, including the small sample size analyzed and the lack of a universally accepted clinical diagnosis of OIAI.…”
mentioning
confidence: 63%